THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PRODUCTIVITY PT DUTA MEANS OF SCIENCE YOGYAKARTA - Kuswarjanti, Sri; Lantum, MS, Drs. Alex Kahu (Management, 2010)
This study aims to determine the profile of respondents, to determine the leadership style that is applied and also to determine the effect of leadership style on the productivity of workers at PT Duta Sarana Science. In this study using simple linear regression analysis with a sample of 50 respondents. From the results of data analysis known that the leadership of the force effect on labor productivity showed a positive effect. The study provides evidence that the valuation effects of leadership style on employee productivity is positive. This indicates that the indicators in the style of leadership has an important role in influencing employee productivity. Keywords: Leadership style